2019
DOI: 10.3390/min9070452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Comminution Methods on Low-Rank Coal Bubble–Particle Attachment/Detachment: Implications for Flotation

Abstract: The floatability of fine low-rank coal particles can be greatly influenced by their morphological characteristics, such as shape and surface roughness. In this study, the attachment efficiency and detachment amplitude of fine low-rank coal particles produced by various comminution methods onto/from the bubble surface were investigated using homemade bubble-particle wrap angle and bubble-particle attachment/detachment testing systems. Results showed that the length-diameter ratio of rod-milled products was smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This suggested that the difference of wettability between apatite and dolomite could be enlarged by adjusting the surface roughness of them, and then the difference of floatability between them was expected to enlarge to strengthen the flotation separation. Previous studies [7,[9][10][11]26,46,47] had also proven that this insight was feasible, in which the size and shape of mineral particles could be changed by controlling grinding, thus affecting their surface roughness. Grinding the malachite with quartz can improve the surface roughness of malachite particles, and then improve its floatability [22].…”
Section: Effect Of Surface Roughness On Contact Angle Of Apatite and mentioning
confidence: 95%
“…This suggested that the difference of wettability between apatite and dolomite could be enlarged by adjusting the surface roughness of them, and then the difference of floatability between them was expected to enlarge to strengthen the flotation separation. Previous studies [7,[9][10][11]26,46,47] had also proven that this insight was feasible, in which the size and shape of mineral particles could be changed by controlling grinding, thus affecting their surface roughness. Grinding the malachite with quartz can improve the surface roughness of malachite particles, and then improve its floatability [22].…”
Section: Effect Of Surface Roughness On Contact Angle Of Apatite and mentioning
confidence: 95%
“…Several separation methods, such as magnetic aspiration, gravity separation, bio-beneficiation and froth flotation, have been developed to facilitate clean and efficient utilization of low-rank coal. Compared with other separation methods, froth flotation is an effective separation method for fine coal cleaning, which depends upon the differences in the surface properties of coal and gangue minerals [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to mineral liberation, two aspects must be addressed: (1) the characterization of the raw materials to be processed, and (2) the variation of the liberation characteristics according to the treatment to reduce the particle size. This issue covers both topics: techniques of mineral liberation characterization of ores before treatment [2,3], and the relationships between comminution and mineral liberation, taking into account the energy consumption [4][5][6][7][8].…”
mentioning
confidence: 99%